Bibliometric Research on Social Interaction in Virtual Worlds - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a bibliometric analysis of research on social interaction in virtual worlds, highlighting key trends, thematic clusters, and global collaborations. By analyzing co-authorship networks, keyword co-occurrences, and publication trends, this research identifies the evolution of scholarly interest in the field. Early studies focused on identity formation, social presence, and psychological aspects of virtual interactions, while recent research has shifted towards artificial intelligence, virtual reality, and human-computer interaction. The findings indicate that virtual social interactions are increasingly shaped by technological advancements, necessitating further examination of their ethical, psychological, and societal implications. The co-authorship analysis reveals strong international collaborations, with the United States, Germany, and Italy playing dominant roles, while emerging research hubs in Asia contribute to the field’s globalization. Future research should address ethical concerns surrounding AI-driven interactions, the effects of immersive technologies on social behavior, cross-cultural variations in virtual communication, and the need for longitudinal studies on digital socialization. This study provides a structured overview of the research landscape, offering insights into emerging trends and future directions in the study of social interactions in virtual worlds.